Knowledge management: organizational approach for the development of innovative capacity in SENA - Cuello Cuello, Jaime
This article seeks to analyze knowledge management as an organizational approach for the development of innovative capacity in SENA, in order to give an adequate management to the Knowledge Management System, to give support to the incorporation of knowledge and technologies. generating capacity to innovate, with external knowledge acquisitions and capital goods as part of R & D. In this bibliographical and documentary research, the proposals made are part of a theoretical review based on the opinion of several authors with significant contributions of knowledge management and innovation. In conclusion, it can be inferred that when sharing knowledge, various collaboration programs should be developed, where participants can contribute their knowledge by forming collaborative networks, promoting the culture of knowledge in the organization with activities related to the appropriation, use and sharing of knowledge as a transcendental part of the Innovation process.